O ensino de patologia clínica/medicina laboratorial nas escolas médicas de Minas Gerais - Thiago Rezende Ferreira (2020)
Clinical Pathology/Laboratory Medicine (PC/ML) is the medical specialty that deals with laboratory tests providing important information to health professionals. Literature data indicate that up to 70% of medical decisions are based on complementary exams. Skills in PC/ML is important for the proper use of laboratory tests, and must be given in all medical schools. Objective: The aim of this study is to describe and analyze the clinical pathology instruction at medical schools of the state of Minas Gerais, Brazil. Methods: In this cross-sectional study, a questionnaire was sent by e-mail to each of the coordinators of 33 medical schools from Minas Gerais, Brazil. The following characteristics were assessed: teaching model and activity; hour load; practical activity; evaluation methods; professionals involved; others activities and teaching difficulties in clinical pathology. Results: Of the 33 questionnaires sent, 18 (54.5%) were completed and returned. Of those 18 responses, 7 (38.9%) were from public medical schools, whereas 11 (61.1%) were from private medical schools. The insertion of clinical pathology into course curriculum was observed in all of 18 medical schools, majority in the third year. Teaching took place in different methods and activities: mandatory, optional subjects, discussions of clinical cases and problem situations, modular activities, expository classes and seminars. The workload was variable. Practical classes were offered in less than half of the schools, basically with quick tests and reading slides from biological materials. Most did not offer visits to clinical laboratories. The evaluation methods occurred mainly by presentation of work, discussion of clinical cases and theoretical and practical tests. Half of the schools featured Clinical Pathologists on the faculty. The main complementary activities were monitoring and scientific initiation and few had academic leagues and curricular internships. The main difficulties were lack of professional teaching qualifications, scarcity of teaching materials and students' lack of interest in understanding the principles of laboratory medicine. Conclusions: The teaching of clinical pathology is present in all medical schools evaluated in Minas Gerais, but in a heterogeneous way, with very different teaching-learning methods and activities. Due to its importance in medical training, the teaching of clinical pathology should be the subject of permanent analysis and curriculum review, aiming at the training of general practitioners and the programs of the Ministry of Health.